Suppression of Myocardial Hypoxia-Inducible Factor-1α Compromises Metabolic Adaptation and Impairs Cardiac Function in Patients With Cyanotic Congenital Heart Disease During Puberty. Issue 23 (5th March 2021) - Liu, Yiwei; Luo, Qipeng; Su, Zhanhao; Xing, Junyue; Wu, Jinlin; Xiang, Li; Huang, Yuan; Pan, Haizhou; Wu, Xie; Zhang, Xiaoling; Li, Jun; Yan, Fuxia; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Cyanotic congenital heart disease (CCHD) is a complex pathophysiological condition involving systemic chronic hypoxia (CH). Some patients with CCHD are unoperated for various reasons and remain chronically hypoxic throughout their lives, which heightens the risk of heart failure as they age. Hypoxia activates cellular metabolic adaptation to balance energy demands by accumulating hypoxia-inducible factor 1-α (HIF-1α). This study aims to determine the effect of CH on cardiac metabolism and function in patients with CCHD and its association with age. The role of HIF-1α in this process was investigated, and potential therapeutic targets were explored. Methods: Patients with CCHD (n=25) were evaluated for cardiac metabolism and function with positron emission tomography/computed tomography and magnetic resonance imaging. Heart tissue samples were subjected to metabolomic and protein analyses. CH rodent models were generated to enable continuous observation of changes in cardiac metabolism and function. The role of HIF-1α in cardiac metabolic adaptation to CH was investigated with genetically modified animals and isotope-labeled metabolomic pathway tracing studies. Results: Prepubertal patients with CCHD had glucose-dominant cardiac metabolism and normal cardiac function. In comparison, among patients who had entered puberty, the levels of myocardial glucose uptake and glycolytic intermediates were significantly decreased, but fatty acids were significantly increased, along with decreased left ventricular ejection fraction. These clinical phenotypes were replicated in CH rodent models. In patients with CCHD and animals exposed to CH, myocardial HIF-1α was upregulated before puberty but was significantly downregulated during puberty. In cardiomyocyte-specific Hif-1α –knockout mice, CH failed to initiate the switch of myocardial substrates from fatty acids to glucose, thereby inhibiting ATP production and impairing cardiac function. Increased insulin resistance during puberty suppressed myocardial HIF-1α and was responsible for cardiac metabolic maladaptation in animals exposed to CH. Pioglitazone significantly reduced myocardial insulin resistance, restored glucose metabolism, and improved cardiac function in pubertal CH animals. Conclusions: In patients with CCHD, maladaptation of cardiac metabolism occurred during puberty, along with impaired cardiac function. HIF-1α was identified as the key regulator of cardiac metabolic adaptation in animals exposed to CH, and pubertal insulin resistance could suppress its expression. Pioglitazone administration during puberty might help improve cardiac function in patients with CCHD.